1999
DOI: 10.1111/j.1744-7976.1999.tb00446.x
|View full text |Cite
|
Sign up to set email alerts
|

Technical Efficiency, Technological Change and Output Growth of Wheat Farms in Saskatchewan

Abstract: This paper utilizes recent advances in stochastic decomposition methodology to examine the level and the driving forces of technical efficiency for an unbalanced panel data set of 100 wheat farms in Saskatchewan during the period 1987-95. The contributions of resource use and total factor productivity to the output growth of these farms are also investigated. The analysis indicates moderate levels of technical efficiency and a considerable variation of efficiency ratings among Saskatchewan farms. The ownership… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
3
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 21 publications
3
47
3
8
Order By: Relevance
“…Cost of fertilizers or investment on fertilizers was found to be negatively affecting technical inefficiency of barley farmers at less than 1% significance level, indicating investing more in fertilizers will improve barley productivity. Giannakas et al (2001) reported similar results.…”
Section: Estimation Of Productivity Parameters and Determinant Factorssupporting
confidence: 78%
“…Cost of fertilizers or investment on fertilizers was found to be negatively affecting technical inefficiency of barley farmers at less than 1% significance level, indicating investing more in fertilizers will improve barley productivity. Giannakas et al (2001) reported similar results.…”
Section: Estimation Of Productivity Parameters and Determinant Factorssupporting
confidence: 78%
“…Other results indicate the existence of a positive relation between technical efficiency levels and the degree of specialization in the activity (Giannakas et al, 2001). Due to the fact that wheat is a homogenous crop in terms of its attributes, the economic efficiency could be reached when economies of scale are achieved.…”
Section: Resultsmentioning
confidence: 97%
“…Similarly, Tian and Wan (2000) analyzed the determinants of technical efficiency associated to rice, wheat (Triticum aestivum L.) and maize (Zea mays L.) production in China, finding evidence of a positive relation between education and efficiency in the case of wheat and maize and a direct relation with farm size and the adoption of a multiple crop system in the case of rice production. More information on wheat crop efficiency can be found in Battese et al (1993), Battese and Broca (1997), Giannakas et al (2001) and Ahmad et al (2002).…”
Section: Stochastic Frontier Production Functionmentioning
confidence: 99%
“…Rezitis et al, 2003;Emvalomatis et al, 2008), or the share of farm income stemming from government support (e.g. Giannakas et al, 2001), or a ratio relating the amount of subsidies to the level of output or gross margin in order to avoid size effects (e.g. Hadley, 2006;Zhu et al, 2008a andBojnec and Latruffe, 2009;Fogarasi and Latruffe, 2009;Bakucs et al, 2010).…”
Section: Government Intervention In the Agricultural Sectormentioning
confidence: 99%